How far are we from being close? Scopes of the arbitrability of antitrust law and approximations in Peru - Robles Vargas, Antonio (2020)
In recent years, arbitration has been an alternative route to judicial proceedings, especially in commercial disputes. This, as a result of its lottery, for its flexibility, speed, confidentiality, among other aspects. Nonetheless, part of the doctrine considers that this route is not suitable for private disputes relating to matters of antitrust law. In this article, the authors assess the scope of arbitrability, in private matters, on antitrust law in Peru. Thus, they examine whether the courts may interpret compliance with antitrust laws and subsequently issue a ruling on civil liability resulting from this analysis. In this regard, they analyze the most important concepts on the arbitrability of antitrust law, identify the most relevant issues related to the arbitration of antitrust law and, finally, review some Peruvian cases to identify the barriers that make it impossible to arbitral practice on antitrust law in Peruvian law.